The Effects Of E. fetida and R. erythropolis on Soil Microorganisms Activity and Soil Properties in Agrochemical Contaminated Soil - A. A Amin; A. A Jaziri; M. I Syafi`I; A. Kurniawan (Nusantara Science and Technology Proceedings)
Soil microorganisms are one of soil fertility indicator which they have a contribution on soil fertilization. They have an important role in nutrient cycling in the soil. In previous study, we found very low level of soil microorganisms activity in agricultural fields with long-term agrochemicals use. This study was aimed to know responses organisms (E. fetida) and R. erythropolis on soil microorganisms activity and soil properties in agrochemical contaminated soil. The soil sample was mixture by 1% organic material (w/w) as the base soil treatment, then soil was treated by E. fetida, R. erythropolis (ER) and without addition as the control (CER). Analysis of total bacterial number was analyzed by using Environmental DNA, analysis of chemical properties was consisted of total carbon (TC), total nitrogen (TN), total phosphorous (TP) and total potassium (TK). The results show that soil sample had a very low bacterial number (< 6.6 ×106 cells/g-soil). The soil was treated by earthworm (E. fetida) and R. erythropolis. After four weeks treatment, soil microorganisms number in control treatment increased up to 3.5 ×108 cells/g-soil, while treatment earthworm and R. erythropolis increased of soil microoganisms number up to 4.5 ×108 cells/g-soil. On the other hand, ER can increase of chemical properties such as, total carbon, total nitrogen, total potassium and total phosphorous. Analysis of PCR-DGGE showed that E. fetida and R. erythropolis can modify of soil microorganisms community. These results were found that earthworms and R.erythropolis treatment was rapidly enhancing not only soil microorganisms number and community but also on soil properties in agrochemical-contaminated soils.